A corpus linguistic study of constructional equivalence for the Indonesian translation of ROB and STEAL based on the OpenSubtitles Parallel Corpus - Gede Primahadi Wijaya Rajeg; I Made Rajeg (PAROLE: Journal of Linguistics and Education, 2022)
Catford’s (1965) classic idea in translation theory indicates the measurability of translation equivalence. Following up on this idea, this paper offers a case study to measure the translation equivalence of English verbal near-synonyms ROB and STEAL (R&S), especially the equivalence at the constructional level. Adopting a quantitative corpus linguistic method and the Construction Grammar approach, we analyse random usage samples of R&S from English-Indonesian parallel corpus for the degree of constructional equivalence along two dimensions: (i) the profiled participant roles and (ii) the grammatical construction types of these verbs. We discover that the Indonesian translations maintain a high degree of equivalences along these dimensions, albeit with few variations. This suggests that the translators attempt to be as faithful as possible to the source texts. Furthermore, our study reveals the translation norms/typicality in how the constructional profiles of the near-synonyms R&S are translated into Indonesian. The paper generally seeks to demonstrate how such a central notion as equivalence in translation studies can be investigated using parallel corpora and the quantitative corpus linguistic method.